Efficacy of CLT4A variants as immunoregulatory molecules among Vitiligo patients in Saudi Arabia - Amal F. Alshammary; Ghada BinSaif; Imran Ali Khan (Scientific Reports)
Abstract Vitiligo is a skin depigmentation condition caused by the immune-mediated perdition of melanocytes. In vitiligo, cytotoxic T-lymphocytes damage melanocytes, causing skin depigmentation. The Cytotoxic T-Lymphocyte Antigen 4 (CTLA-4) gene has been reported to be related to vitiligo and other autoimmune diseases. The purpose of this study was to explore the molecular involvement of rs231775 and rs3087243 SNPs in the CTLA4 gene in vitiligo patients. The recruitment was based on the sample size calculation and based on it, we have recruited 300 Saudi individuals who were evenly divided into vitiligo cases and controls. Extracted genomic DNA was utilized to amplify rs231775 and rs3087243 SNPs in the CTLA4 gene, which were subsequently digested and verified using Sanger sequencing. The polymerase chain reaction and restriction fragment length polymorphism analysis laboratory data were stored in Excel and used for further statistical analysis. Although baseline details had no correlation (p > 0.05) between the two groups, Hardy-Weinberg Equilibrium analysis was in agreement with the vitiligo patients (p > 0.05). The genotype and allele frequencies were frequently associated (p < 0.05) with rs3087243, and rs231775 SNP showed a nominal association with GG genotype and G allele (p < 0.05). The specific relationship in vitiligo cases was revealed by MDR, GDMR, and linkage disequilibrium (p < 0.05), but not with haplotype analysis (p > 0.05). Thus, the study concluded that rs3087243 SNP was associated and rs231775 SNP showed a nominal association with vitiligo in the Saudi population.